A replicon RNA vaccine can induce durable protective immunity from SARS-CoV-2 in nonhuman primates after neutralizing antibodies have waned. - Megan A O'Connor; David W Hawman; Kimberly Meade-White; Shanna Leventhal; Wenjun Song; Samantha Randall; Jacob Archer; Thomas B Lewis; Brieann Brown; Megan N Fredericks; Kaitlin R Sprouse; Hillary C Tunggal; et al. (PLoS Pathogens)
The global SARS-CoV-2 pandemic prompted rapid development of COVID-19 vaccines. Although several vaccines have received emergency approval through various public health agencies, the SARS-CoV-2 pandemic continues. Emergent variants of concern, waning immunity in the vaccinated, evidence that vaccines may not prevent transmission and inequity in vaccine distribution have driven continued development of vaccines against SARS-CoV-2 to address these public health needs. In this report, we evaluated a novel self-amplifying replicon RNA vaccine against SARS-CoV-2 in a pigtail macaque model of COVID-19 disease. We found that this vaccine elicited strong binding and neutralizing antibody responses against homologous virus. We also observed broad binding antibody against heterologous contemporary and ancestral strains, but neutralizing antibody responses were primarily targeted to the vaccine-homologous strain. While binding antibody responses were sustained, neutralizing antibody waned to undetectable levels in some animals after six months but were rapidly recalled and conferred protection from disease when the animals were challenged 7 months after vaccination as evident by reduced viral replication and pathology in the lower respiratory tract, reduced viral shedding in the nasal cavity and lower concentrations of pro-inflammatory cytokines in the lung. Cumulatively, our data demonstrate in pigtail macaques that a self-amplifying replicon RNA vaccine can elicit durable and protective immunity to SARS-CoV-2 infection. Furthermore, these data provide evidence that this vaccine can provide durable protective efficacy and reduce viral shedding even after neutralizing antibody responses have waned to undetectable levels.